Ising model with competing "Uncle-Nephew" interaction - Ganikhodjaev, Nasir (2015)
Consideration of spin models with multispin interactions has proved to be fruitful in many fields of physics. The axial next-nearest-neighbour Ising (ANNNI) model on Z 2 , which consists of an Ising model with nearest-neighbour interactions augmented by competing next-nearest-neighbour couplings acting parallel to a single axis direction originally introduced by Elliot [1], is perhaps the simplest nontrivial model displaying a rich phase diagram with a Lifshitz point and many spatially modulated phases. On the basis of numerical mean-field calculations, Bak and von Boehm [2] suggested the existence of an infinite succession of commensurate phases, the so-called devil’s staircase, at low temperatures.